Penerapan Terapi Latihan Buerger Allen terhadap Tekanan Darah pada Lansia Penderita Hipertensi di Kelurahan Joyotakan - Adelia Arina Manasikana; Norman Wijaya Gati (An-Najat, 2024)
Hypertension or high blood pressure is a disorder of the walls of blood vessels that increases blood pressure, resulting in the supply of oxygen and nutrients not being able to reach the tissues that need them. The Buerger Allen exercise is an exercise pattern to normalize the arteries of the lower limbs by using. To determine the application of Buerger Allen exercise therapy to reduce high blood pressure in the elderly in Joyotakan Village. This type of research is a case study that uses descriptive pretest posttest design research methods and uses the Buerger Allen SOP. The results of application to 2 respondents carried out for 2 days with a frequency of 15 minutes a day showed the influence of Buerger Allen exercise therapy on blood pressure in elderly people with hypertension. There are differences in results before and after the intervention of Buerger Allen exercise therapy on blood pressure in elderly people with hypertension